Endomarketing: um estudo de caso em uma empresa do Polo Industrial de Manaus - Campos Neto, Raimundo Ribeiro (Brasil, 2024)
This article presents a study on the analysis of the employees' perception of the Endomarketing practices used by a company in the Manaus Industrial Complex. The methodology used was qualitative research whose data were collected from interviews with a semi-structured script with 5 employees. The technique used to interpret the individuals' discourses was content analysis. In this context, the results show that the company emphasizes the importance of clarity in the interpretation of endomarketing by employees and the need for effective strategies for its implementation, also highlighting the crucial role of internal communication in organizations. In addition, it should be noted that the suggestions of the study participants can enrich endomarketing and internal communication. The importance of flexible and adaptive approaches to strengthen organizational culture and employee engagement is highlighted. The endomarketing practices analyzed in this study may serve as references for further deepening in the field of endomarketing and internal communication.